MiR-29c down-regulation is associated with disease aggressiveness and poor survival in Chinese patients with chronic lymphocytic leukemia. Issue 7 (July 2014) - Zhou, Keshu; Yu, Zhen; Yi, Shuhua; Li, Zengjun; An, Gang; Zou, Dehui; Qi, Junyuan; Zhao, Yaozhong; Qiu, Lugui
Abstract Aberrant expression of microRNAs in chronic lymphocytic leukemia (CLL) has been reported to be associated with clinical outcome and improve prognostic stratification. The aim of this study was to explore the association of miR-29c expression with clinical parameters and survival in 53 Chinese patients with CLL. We showed that the miR-29c expression level decreased significantly from early to advanced clinical stages, and was significantly lower in patients with β2-microglobulin higher than 3.5 mg/L or with disease progression or death. With the cut-off determined by receiver operating characteristic (ROC) curve analysis, optimizing concordance with immunoglobulin heavy chain (IgVH) mutation status, miR-29c negative and positive groups were defined as including 17 and 36 patients, respectively. The miR-29c negative group had a higher percentage of patients with trisomy 12 or deletion of 11q or 17p (70.6% vs. 34.3%; p = 0.014) compared to the miR-29c positive group. The median progression-free survival and overall survival of the miR-29c negative group were 21 and 92 months, respectively, significantly shorter than in the miR-29c positive group (both not reached; p = 0.002 and p = 0.042, respectively), and miR-29c down-regulation was an independent prognostic factor for PFS. In conclusion, down-regulation of miR-29c is associated with higher tumor burden and significantly predicts short survival in Chinese patients with CLL.